2011
DOI: 10.1504/ijpqm.2011.043010
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the productivity of knowledge workers: a case study from an Iranian Oil Company

Abstract: This study aimed at studying factors influencing the productivity of knowledge workers at the Iranian Oil Company (IOC) through factor analysis. Ninety experts working at the staff units of IOC were selected and responded to a researcher-made questionnaire. This questionnaire, the reliability of which was confirmed by Cronbach , included 50 items. Findings were analysed through second-order factor analysis using LISREL software. Findings revealed job satisfaction and capability were the individual factors whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Researchers in productivity measurement from Iran have also noted: "Labor productivity is the result of worker ability and promotion" (Salehi et al, 2013, p. 58). Noruzy et al (2011) carrying out a case study on an Iranian Oil Company have discovered that job satisfaction and employees' abilities are the individual factors that affect the labor productivity; participation, education, motivation and communication -organizational factors, but clarity of employees' role, challenging work and autonomy are the professional factors that affect productivity in the studied enterprises (Noruzy et al, 2011). Choosing between technological factors or the human resource factor to achieve the company's performance, including the issue of productivity increase, the entrepreneur and one of the most socially active representatives of the Latvian business environment Vīksna (2009) has pointed out that the enterprise's efficiency can be increased in various ways -optimizing costs, reviewing the customer database, introducing the latest technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers in productivity measurement from Iran have also noted: "Labor productivity is the result of worker ability and promotion" (Salehi et al, 2013, p. 58). Noruzy et al (2011) carrying out a case study on an Iranian Oil Company have discovered that job satisfaction and employees' abilities are the individual factors that affect the labor productivity; participation, education, motivation and communication -organizational factors, but clarity of employees' role, challenging work and autonomy are the professional factors that affect productivity in the studied enterprises (Noruzy et al, 2011). Choosing between technological factors or the human resource factor to achieve the company's performance, including the issue of productivity increase, the entrepreneur and one of the most socially active representatives of the Latvian business environment Vīksna (2009) has pointed out that the enterprise's efficiency can be increased in various ways -optimizing costs, reviewing the customer database, introducing the latest technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Palčic et al (2010) study it is confirmed that teamwork in production is one of the most widely used organizational innovation concepts in Slovenian manufacturing enterprises (Palčic et al, 2010), while a study in manufacturing enterprises in Germany has found that almost 2/3 of manufacturing enterprises apply teamwork and a positive relationship between flexibility, complexity, new products, organizational concepts and the introduction of teamwork in production has been indicated (Bikfalvi, 2011). Islam and Syed Shazali (2011) while studying the levels of skills, impact of a favourable work environment and R&D on the productivity of manufacturing-intensive industries, have found that productivity is positively related to a favourable work environment (Islam & Syed Shazali, 2011), but the study of the Iranian Oil Company has found a link between productivity and such teamwork characteristics as participation, communication in the enterprise, clarity of the role, challenging work and autonomy (Noruzy et al, 2011). Whereas a study by Munyai et al (2018) has found that there is a strong link between the organizational culture of efficiency and productivity improvement in cable manufacturing processes (Munyai et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations